Review of Arthur M. Jacobs, Neurocomputational Poetics. How the Brain Processes Verbal Art (Anthem Press, 2023) (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2024)
Review of Arthur M. Jacobs, Neurocomputational Poetics. How the Brain Processes Verbal Art. Anthem Press, 2023.